TSHD ship opening simulation by discrete element method. (January 2020) - Andrun, M.; Ban, D.; Bašić, J.; Ljubenkov, B.
Highlights: Cargo discharge through symmetrical and non-symmetrical hopper openings influences the ship stability. Stability of the ship needs to be dynamically assessed when analyzing cargo discharge. The dynamics of gravel discharge process can be efficiently simulated by Discrete Element Method (DEM). Numerical simulations indicate that environmental loads, combined with a hull opening failure, could lead to the ship catastrophe. Graphical abstract: Abstract: This article studies a Split Trailing–Suction Hopper Dredger (Split TSHD) with longitudinally-split hull, which symmetrically opens for gravity-driven unloading of the cargo while being exposed to various environmental conditions. Regular and failure hull openings are numerically simulated to investigate the ship stability and safety of cargo discharge procedures. Unsteady simulations of discharging were performed by the Discrete Element Method, while the ship hydrostatic properties are calculated using Radial Basis Functions. The dynamics of the righting moment and arm are simulated, which are affected by the cargo dynamics and the loss of displacement. Results of the numerical simulations indicate that cargo dynamics during the discharge should not be ignored, as it affects ship's transverse stability. An incoming wave combined with an opening failure of the hull could lead to serious loss of transverse stability.